Biogenesis and activity regulation of protein phosphatase 1. (8th February 2017) - Verbinnen, Iris; Ferreira, Monica; Bollen, Mathieu
Abstract : Protein phosphatase 1 (PP1) is expressed in all eukaryotic cells and catalyzes a substantial fraction of phosphoserine/threonine dephosphorylation reactions. It forms stable complexes with PP1-interacting proteins (PIPs) that guide the phosphatase throughout its life cycle and control its fate and function. The diversity of PIPs is huge (≈200 in vertebrates), and most of them combine short linear motifs to form large and unique interaction interfaces with PP1. Many PIPs have separate domains for PP1 anchoring, PP1 regulation, substrate recruitment and subcellular targeting, which enable them to direct associated PP1 to a specific subset of substrates and mediate acute activity control. Hence, PP1 functions as the catalytic subunit of a large number of multimeric holoenzymes, each with its own subset of substrates and mechanism(s) of regulation.